A Study on the Improvement of Nursing Interruption Risk by a Closed-Loop Management Model - Zhang WG; Liu JW; Yang SY; Wang QQ; Liu CX; Li Y (Dove Medical Press, 2021)
Wen-Guang Zhang,1 Jia-Wei Liu,2 Su-Yun Yang,3 Qiao-Qian Wang,4 Chen-Xing Liu,2 Yao Li2 1Department of Nursing, The First Hospital of Shanxi Medical University, Taiyuan, 030000, People's Republic of China; 2School of Nursing, Shanxi Medical University, Taiyuan, 030000, People's Republic of China; 3Department of Nuclear Medicine, The First Hospital of Shanxi Medical University, Taiyuan, 030000, People's Republic of China; 4Department of Hypertension, The First Hospital of Shanxi Medical University, Taiyuan, 030000, People's Republic of ChinaCorrespondence: Su-Yun YangDepartment of Nuclear Medicine, The First Hospital of Shanxi Medical University, Room 601, Unit 8, Building 1, No. 8 Wenyuan Lane, Yingze District, Taiyuan, 030000, People's Republic of ChinaTel +8613603512029Email syy_dr09sun@163.comObjective: This study aimed to evaluate the effect of closed-loop management on nursing disruption risk.Methods: Using a quasi-experimental research method, convenient sampling was used to extract 20 nurses working at our hospital as the research objects. The control group members were selected from January to March 2018 via the traditional method, and the experimental group members were selected from April to June 2018 via the closed-loop management method. At three months before and after the implementation of the management model, a self-designed quantitative test form and satisfaction questionnaire were used to analyze the frequency of nursing disruption events, the accuracy rate of doctors' advice, the average drug delivery time of the static distribution center, the implementation rate of personal digital assistant (PDA) code scanning, and the report rate of risk-outcome nursing disruption events.Results: After the implementation of the management model, the frequency of nursing disruptions and average drug delivery time of the static distribution center were significantly lower than before, and the differences were statistically significant (p < 0.05). Moreover, the accuracy rate of doctors' advice, the implementation rate of PDA code scanning, and the reporting rate of risk-outcome nursing disruption events were significantly higher than before, and these differences were statistically significant as well (p < 0.05).Conclusion: The application of a closed-loop management model could significantly reduce the occurrence and optimize the outcomes of nursing disruption events and improve the work processes of medical care.Keywords: closed-loop management, nursing interruption, risk control, personal digital assistant, PDA, management mode